EP.TU.517Is a foundation interim year one post better for improving confidence in the care of the dying in general surgery in a tertiary centre or a district general hospital?. (28th October 2021) - George, Jayan; Mathew, Alok; Robinson, Edward; Botsford, Edward; Ardley, Rohan; Al-Mukhtar, Ahmed
Abstract: Aims: 1. Understand the confidence levels of current foundation year one (FY1) doctors who have had foundation interim year one (FiY1) post in a tertiary centre (TC) and a district general hospital (DGH). 2. Determine whether there is a difference in the experience of the FiY1 post in a TC or DGH. Methods: FY1s were surveyed throughout August – December 2020. Six questions used Likert scales (1 to 5: not at all confident to very confident) over some common palliative themes. Data was initially inputted using Google Docs and analysed in Microsoft Excel. Results: 16.7% (4/24) from a DGH and 83.3% (20/24) from a TC had a FiY1 post. Confidence levels were higher for FY1s who had a FiY1 post in a TC than a DGH in managing pain control, psychological distress, spiritual health. Confidence levels were higher for FY1s who had a FiY1 post in a DGH than a TC in dealing with social issues, speaking to the family of a patient in the last days of life. Conclusions: FY1s who had a FiY1 post in a TC had better confidence in three areas as opposed to a DGH in two areas. The experience of the FiY1 should be more standardised to ensure the growth of confidence across all areas identified in the survey.